2016
DOI: 10.21037/acs.2016.08.06
|View full text |Cite|
|
Sign up to set email alerts
|

Ravitch versus Nuss procedure for pectus excavatum: systematic review and meta-analysis

Abstract: Background: Pectus excavatum is the most common congenital chest wall deformity. The two most common surgical techniques for its correction are the modified Ravitch technique and the minimally invasive Nuss technique. Despite both procedures being used widely, data comparing them are scarce. Methods:We conducted a systematic review and meta-analysis of comparative studies to evaluate these procedures. A systematic search of the literature was performed from six electronic databases. Pooled metaanalysis was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 29 publications
0
44
0
1
Order By: Relevance
“…However, more severe pectus defects, especially when coupled to scoliosis, can cause clinically consequential restrictive disease [177]. Less invasive and more customizable surgical options (e.g., vertical expandable prosthetic titanium ribs (VEPTR) magnetic rods, or Nuss bars) for both scoliosis and pectus deformities are now employed early in disease development leading to fewer complications and lung function stabilization in selected patients [178][179][180][181][182]. As yet, no long-term studies documenting stability or improvement in lung function with these newer interventions in the Marfan population are available.…”
Section: Restrictive Lung Diseasementioning
confidence: 99%
“…However, more severe pectus defects, especially when coupled to scoliosis, can cause clinically consequential restrictive disease [177]. Less invasive and more customizable surgical options (e.g., vertical expandable prosthetic titanium ribs (VEPTR) magnetic rods, or Nuss bars) for both scoliosis and pectus deformities are now employed early in disease development leading to fewer complications and lung function stabilization in selected patients [178][179][180][181][182]. As yet, no long-term studies documenting stability or improvement in lung function with these newer interventions in the Marfan population are available.…”
Section: Restrictive Lung Diseasementioning
confidence: 99%
“…When the costal arch deformity exists with other abnormalities, such as pectus excavatum and puctus carinatum, the deformity can be treated at the same time. The early used method was to remove partial rib arch, and then connect the residual cartilage structures [1]. In 2010, Bosgraaf and colleague introduced a technique for treatment of costal arch deformity after Nuss operation [3].…”
Section: Commentmentioning
confidence: 99%
“…In all kinds of thoracic deformities, pectus excavatum and puctus carinatum are the relatively more common kinds [1]. Other deformities are rarely mentioned, and costal arch deformity is one of them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[8][9][10] In addition, recent studies have suggested that minimal invasive repair of PE improves the quality of life, body image, and the patient's self-esteem. 15,16,[18][19][20] To engage in light physical exercise such as jogging and cycling slowly according to his pace Patient's information: A 12-year-old boy with his parents visited our department's pediatric cardiac and thoracic outpatient clinic at the province city hospital in the background of severe recurrent chest pain accompanied by chest tightness. The patient was tall, thin with clear consciousness denied any trauma to the chest and was also not on any medications and at the time of visit he was not in any acute distress what so ever.…”
Section: Introductionmentioning
confidence: 99%